The Effect Of Earnings Management On Tax Avoidance, Environmental Social Governance (Esg) Disclosure As The Moderating Variable - Sari, Tarisya Wahyu Permata; Hariadi, Bambang (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This quantitative study aims to examine the effect of earnings management on tax avoidance and the moderating role of environmental social governance (ESG) disclosure in this relationship. A non-probability sampling method with a purposive sampling technique was employed, resulting in a sample of 46 manufacturing companies listed on the Indonesia Stock Exchange during the 2018–2022 period. Multiple linear regression analysis and moderated regression analysis (MRA) were used to process 206 sample observations with the assistance of SPSS. The findings indicate that earnings management does not have a direct effect on tax avoidance, and that ESG disclosure among manufacturing firms is proven to weaken the effect of earnings management on tax avoidance. Therefore, increasing transparency and accountability through ESG disclosure serves as a control mechanism against unethical corporate practices, thereby helping to maintain the positive image and reputation that have been established.